Practical cataloguing : AACR, RDA and MARC21 - Welsh, Anne , 1972-; Batley, Sue (Facet Publishing, 2012)
Written at a time of transition in international cataloguing, this book provides cataloguers and students with a background in general cataloguing principles, the code (AACR2) and format (MARC 21) and the new standard (RDA). It provides library managers with an overview of the development of RDA in order to equip them to make the transition